THROMBOTIC AND BLEEDING RISK FACTORS IN ESSENTIAL THROMBOCYTHEMIA - A. A. Zhernyakova; I. S. Martynkevich; V. A. Shuvaev; L. B. Polushkina; M. S. Fominykh; V. Yu. Udal’eva; I. I. Zotova; D. I. Shiсhbabaeva; S. V. Voloshin; S. S. Бессмельцев; A. V. Chechetkin; K. M. Abdulkadyrov (Онкогематология, 2017)
Background. Thrombosis and hemorrhage are the main category of complications, that affects the overall survival (OS), quality of life and therapy option choice in essential thrombocythemia (ET). Molecular marker presence (JAK2V617F (JAK2+), MPL (MPL+), CALR (CALR1+-type 1, CALR2+-type 2) or its absence (triple-negative status (TN)) in ET supposed to impact on the clinical course, thrombosis rate and ET prognosis.The aim of this study was to investigate interactions between the presence of molecular marker, thrombosis/bleeding rates and the OS in ET.Methods. Outpatient’s charts of 240 ET patients, who had been diagnosed with ET at our institution according to WHO 2008 criteria. The following data were assessed: complete blood count, bone marrow biopsy results, bone marrow cytogenetic, the restriction fragment length polymorphism (RFLP) results used for JAK2V617F detection, in case of JAK2V617F-negative status the PCR-RFLP results (MPL detection) and the direct sequencing results (CALR detection). Different thrombotic/bleeding complications rates were analyzed. The OS in ET patients was compared according to complications and IPSET-thrombosis groups. Results. Among 240 pts 183 (76.3 %) hadn’t any thrombotic complication or bleeding event (no complications/NC), 57/240 (23.7 %) had complications: 49/57 (85.9 %) reported arterial or/and venous thrombosis, stroke or heart failure (thrombosis+) and 11/57 (19.3 %) had bleeding events (hemorrhage+). Thrombotic complications in JAK2+ had 27.4 % (50/182) pts, in TN – 30.7 % (8/26) pts, in CALR1+ – 18.2 % (2/11) pts and no cases of thrombosis were detected in CALR2+ and MPL+ subgroups (p < 0,001). There were significant statistical differences in median platelet count as follows: 742 . 10 9/L (thrombosis+) and 937 . 10 9/L (hemorrhage+) (p = 0.003). No significant statistical differences in median hemoglobin and leukocyte count (р = 0.75 and р = 0.47) were detected. There were more than a half pts older than 60 years in groups NC (51 %) and thrombosis+ (59 %) and in group hemorrhage+ only 36 % (p < 0,001). Cardiovascular risk factors were reported in 24 % pts (NC), 69 % pts (thrombosis+) and 36 % pts (hemorrhage+) (p < 0,001). There were no significant statistical differences in follows risk factors as platelets count > 1000 . 10 9/L and leukocytosis > 11 . 10 9/L (р = 0.85 and р = 0.72). No significant differences in OS among groups NC, thrombosis+ and hemorrhage+ (р = 0.21) and IPSET-thrombosis groups (р = 0,068) were found. Conclusion. Along with common thrombotic risk factors (age > 60 and cardiovascular risk factors) mutational status may help to identify ET course. Leukocytosis > 10 . 10 9/L and thrombocytosis > 1000 . 10 9/L cannot be assessed as independent thrombosis risk factors in ET. The JAK2V617F mutation was associated with increased risk of thrombotic complications in ET. CALR mutations were associated with lower thrombosis risk, comparing to JAK2+ status despite the fact of CALR+ patients had higher platelets level.